AKAD NIKAH BAGI PENYANDANG TUNAWICARA MENURUT IMAM SYAFI’I (Studi Kasus di KUA Kecamatan Gondang Kabupaten Mojokerto) - Lala Allifiyah; Muhammad Muhammad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
. The background to this article is based on the village people's lack of knowledge about how to contract marriage for the deaf, especially according to the concept of Imam Syafi'i, where this research took place at the KUA, Gondang District, Mojokerto Regency. The majority of people only know the general procedures for a marriage contract which is done with clear speech, they forget about our brothers and sisters who are limited in speaking. This type of research involves looking directly at the research location or what is usually called field research so that the data obtained is real with that at the location. With a descriptive qualitative approach where the descriptive data is in the form of writing, sayings and actions from the objects observed. The results of this research explain that the marriage ceremony for mute people was carried out at KUA Kec. Gondang uses signs that can be understood, namely nodding the head. This method includes Imam Shafi'i's theory. The obstacle that occurred in this research was a communication problem in which the KUA made efforts to handle this by giving direction to related parties about what should be done.